Tarekat - Ahmad Khoirul Fata (Al-Ulum, 2011)
Sufism as an organized institution service provider presents a practical and structured to guide the stages of mystical journey that centers on student-teacher relationships; authority of the teacher who had climbed the stages of mystical must be completely accepted by a student. This is necessary in order to move students to meet with God can be completely successful. Congregations have been known in the Islamic world, especially in the second century AD 12/13 (6/7 H) with the presence of the congregation Qadiriyah under the founder Abd al-Qadir al-Jailani (1077-1166 AD). After passing through the stages in the congregation, a member will receive a diploma of teaching; one can conduct a congregation and teach others. Genealogically, most congregations linking their lineages to the Prophet Muhammad through Ali ibn Abi Talib, except of the Naqshbandi who through Abu Bakr Siddiq.